1966
DOI: 10.1136/bmj.2.5520.1007
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia due to diazepam.

Abstract: CorrespondenceMEDIBusH 1007to the pump-head, for only in this way can air embolism be prevented. It is not enough to use one clamp only, between the oxygenator and the leak, for air may still enter the tube through the defect due to a Venturi effect as the roller passes over it, and then pass into the patient's arterial system.-We are, etc.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This difference may reflect hypothermia-a known effect of diazepam both in humans and animals. While human data agree with a weak hypothermic effect of diazepam at anxiolytic doses (10-20 mg) (Irvine 1966;Echizenva et al 2004) and these data match decreased oxygen consumption, energy expenditure (Kirvela et al 1994), and enhanced heat loss reported in humans (Echizenva et al 2004), animal data are more controversial. While diazepam decreased body core temperature at low doses in monkeys (0.25 mg/kg; Clark and Lipton 1981), it had no effect on temperature even at higher doses in cats (0.3-1.5 mg/kg; Griauzde et al 1979).…”
Section: State-dependent Effects Of Diazepammentioning
confidence: 51%
See 1 more Smart Citation
“…This difference may reflect hypothermia-a known effect of diazepam both in humans and animals. While human data agree with a weak hypothermic effect of diazepam at anxiolytic doses (10-20 mg) (Irvine 1966;Echizenva et al 2004) and these data match decreased oxygen consumption, energy expenditure (Kirvela et al 1994), and enhanced heat loss reported in humans (Echizenva et al 2004), animal data are more controversial. While diazepam decreased body core temperature at low doses in monkeys (0.25 mg/kg; Clark and Lipton 1981), it had no effect on temperature even at higher doses in cats (0.3-1.5 mg/kg; Griauzde et al 1979).…”
Section: State-dependent Effects Of Diazepammentioning
confidence: 51%
“…Benzodiazepines at higher doses also possess anticonvulsant, sedative, muscle relaxant, and amnestic properties. Although benzodiazepines induce dose-dependent sedation (hypoactivity) and effectively inhibit behavioral responses to various stressful situations in both humans and animals (Clark and Lipton 1981;Echizenva et al 2004;Irvine 1966), their effects on physiological functions appear to be state-dependent. For example, diazepam strongly attenuates hypertensive responses to various stressful stimuli (i.e., restraint, open-field, interspecies social interaction) but has no effects on blood pressure and induces weak tachycardia in a stress-free environment (Conahan and Vogel 1986;Mailliet et al 2001;van den Buuse et al 2001;Valdman and Medvedev 1978).…”
mentioning
confidence: 97%
“…The 'burst-suppression phenomena' reported by Bell (1970) in the EEG of three of his patients never occurred in our studies and may have been due to the larger doses he employed. We did not meet the other complications attributed to diazepam in the literature, such as hypotension and respiratory depression (mentioned by many authors), cardiac arrest (Prensky et al, 1967), hypothermia (Irvine, 1966), abnormal liver function (Parsonage and Norris, 1967), and tonic status epilepticus (Prior et al, 1972).…”
Section: Discussionmentioning
confidence: 77%
“…In our patients, when a small dose of diazepam was sufficient to control the attacks and stop the discharges in the EEG, there was often a slight increase in fast activity, particularly over the anterior half of the two hemispheres. The 'burst-suppression phenomena' reported by Bell (1970) (Prensky et al, 1967), hypothermia (Irvine, 1966), abnormal liver function (Parsonage and Norris, 1967), and tonic status epilepticus (Prior et al, 1972).…”
Section: Resultsmentioning
confidence: 99%
“…Benzodiazepine are widely used drugs against anxiety and muscle rigidity and their toxicity is low. However, they have been found alone and/or with alcohol in accidental hypothermia deaths as a contributory factor (Irvine 1966;Wedin et al 1979). These observations imply that benzodiazepines also could affect thermoregulation in man, as they apparently do in squirrel monkey, especially in the older ones (Clark and Lipton 1981).…”
mentioning
confidence: 96%